Aquisição de fonologia : a influiência do acento e o preenchimento de unidades prosódicas em dados de fala de duas crianças entre 1;0.4 e 2;1.10 de idade, em contato com o português brasileiro falado em Alagoas e Pernambuco. - Payão, Luzia Miscow da Cruz (2010)
The study delves into the influence of accent and segment completion of prosodic units in speech data from two children between the ages of 1;0.4 and 2;1.10 and who were exposed to Brazilian Portuguese spoken in the states of Alagoas and Pernambuco. It was hypothesized that grammatical processing stems from two concurrent movements in opposing directions during phonological acquisition: a centripetal movement triggering segmentation of the prominent syllable and an opposing, centrifugal one aimed at segment completion of prosodic units. These analytical movements imply a hierarchical basis of relationships between its constituent structures, an assumption backed by autosegmental phonology (GOLDSMITH, 1995; CLEMENTS; HUME, 1995; MOTA, 1996) and prosodic phonology (NESPOR; VOGEL, 1986; SCARPA, 1997, 1999a; SANTOS; SCARPA, 2005). The methodology consisted of a observational and descriptive follow-up with parental consent. The children s spontaneous speech while playfully interacting with parents was digitally recorded over a 7-month period. Data showed that identifying word stress favors the handling of phonological material in the stressed syllable under centrifugal action, thus leading to segment completion of both post-tonic and pre-tonic syllables in accordance with the metrical foot of the target word. A tendency towards completion of the syllable structure and distinction of segment classes was seen in the stressed and post-tonic syllables, influenced by the prevalence of words having a trochaic stress pattern. The organizational hierarchy of the language was shown to guide and drive these movements of centripetal-centrifugal analyses that occur at different phonological levels prosodic and segmental.